Para todes: gender-neutrality in the Portuguese language - Auxland, Morrigan (2020)
Portuguese, as a Romance language, has two linguistic genders: masculine and feminine. Although linguistic gender is separate from the social concept of gender, the two accord when one is talking about a person; feminine forms of address, nouns, and adjectives for a woman, and masculine forms for a man. This raises issues when one considers the rising number of people who identify outside of the gender binary, as well as an idea that is becoming increasingly prevalent – that an individual’s gender cannot, and should not, be assumed when it is unknown. There are, therefore, movements that seek to adapt the language, led by gender-nonconforming, nonbinary and transgender individuals; to introduce a third, grammatically-neutral gender, to better suit the needs of the language’s speakers. This thesis seeks to profile and examine the proposed changes to the Portuguese language, with reference to a number of case studies involving the use of the most common proposed practices and the resulting public and academic responses to each.